The Application of Processing Technology for Jelly Candy Made with Lat Sea Grapes in Southeast Maluku Regency - Alfonsina Marthina Tapotubun; Theodora E.A.A. Matrutty; Meigy Nelce Mailoa; Irene Grace Fransina; Elizabeth Juleny Tapotubun; Welly Angela Riry (Institute for Research and Community Services, 2021)
Seagrapes (Caulerpa sp) thrive in the waters of the Kei Islands of Maluku and can be found throughout the year. However, they are hitherto only used as fresh vegetables. It turns out that sea grapes can be processed into various food and non-food products. The results of a field survey in Ohoi Village, Southeast Maluku, reveal that the community only uses lat as a vegetable and has not used lat as a processed food product. One reason is that the people in Ohoi Village are not aware of its health benefits. This indicates that lat in Ohoi Village has not been used optimally as a rawmaterial for the food and beverage industry despite its high nutritional and economic value. It will be beneficial for the coastal women's group in Ohoi Village to receive training on processing and producing lat-based food items. They can increase their knowledge and skills, thereby improving the welfare of coastal communities and their families. This community service aims to take advantage of the potential of lat sea grapes in Ohoi Village, Southeast Maluku, through the application of lat-based jelly candy processing technology, encouraging the coastal women in Southeast Maluku to become lat-based jelly candy entrepreneurs and resultantly increasing their productivity in the long run.